A 'busy day' effect on perinatal complications of delivery on weekends: a retrospective cohort study. Issue 1 (29th July 2016) - Snowden, Jonathan M; Kozhimannil, Katy Backes; Muoto, Ifeoma; Caughey, Aaron B; McConnell, K John
Abstract : Objective: To evaluate whether busy days on a labour and delivery unit are associated with maternal and neonatal complications of childbirth in California hospitals, accounting for weekday/weekend births. Design: This is a population-based retrospective cohort study. Setting: Linked vital statistics/patient discharge data for California births between 2009 and 2010 from the Office of Statewide Health Planning and Development. Participants: All singleton, cephalic, non-anomalous California births between 2009 and 2010 (N=724 967). Main outcomes: The key exposure was high daily obstetric volume, defined as giving birth on a day when the number of births exceeded the hospital-specific 75th percentile of daily delivery volume. Outcomes were a range of maternal and neonatal complications. Results: Several maternal and neonatal complications were increased on high-volume days and weekends following adjustment for maternal demographics, annual hospital birth volume and teaching hospital status. For example, compared with low-volume weekdays, the odds of Apgar <7 on low-volume weekend days and high-volume weekend days were 11% (adjusted OR (aOR) 1.11, CI 1.03 to 1.21) and 29% higher (aOR 1.29, CI 1.10 to 1.52), respectively. High volume was associated with increased odds of neonatal seizures on weekdays (aOR 1.33, CI 1.01 to 1.71) and haemorrhage on weekends (aOR 1.11, CI 1.01 to 1.22). After accounting for between-hospital variation, weekend delivery remained significantly associated with increased odds of Apgar score <7, neonatal intensive care unit admission, prolonged maternal length of stay and the odds of neonatal seizures remained increased on high-volume weekdays. Conclusions: Our findings suggest that weekend delivery is a consistent risk factor for a range of perinatal complications and there may be variability in how well hospitals handle surges in volume.